2021
DOI: 10.1371/journal.pone.0261550
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PET parameters predicting response to radiotherapy for myeloid sarcoma

Abstract: Purpose Positron-emission tomography (PET)-CT has recently been used for diagnostic imaging and radiotherapy for myeloid sarcoma, but there is little research on predicting the response of radiotherapy. The aim of this study was to analyze the association between PET-CT variables and the response to radiotherapy in patients with myeloid sarcoma. Materials and methods This study was conducted in myeloid sarcoma patients who received radiotherapy and PET-CT before and after radiotherapy. The response to radiot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Some studies have focused on the prognostic value of the [ 18 F]FDG PET/CT findings in patients with leukemia; the prognostic significance of extramedullary involvement in leukemia is still being investigated [42]. A total of 12 patients with myeloid sarcoma who received radiotherapy were assessed by [ 18 F]FDG PET/CT before and after treatment [103]. In those patients, high pretreatment SUVmax was related to treatment failure.…”
Section: Other Utilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have focused on the prognostic value of the [ 18 F]FDG PET/CT findings in patients with leukemia; the prognostic significance of extramedullary involvement in leukemia is still being investigated [42]. A total of 12 patients with myeloid sarcoma who received radiotherapy were assessed by [ 18 F]FDG PET/CT before and after treatment [103]. In those patients, high pretreatment SUVmax was related to treatment failure.…”
Section: Other Utilitiesmentioning
confidence: 99%
“…In those patients, high pretreatment SUVmax was related to treatment failure. However, the sample size was small, and further studies in this field are, therefore warranted [103]. Zhao et al .…”
Section: Other Utilitiesmentioning
confidence: 99%
“…Furthermore, the authors noted that there were no significant toxicities associated with the treatment. 58 A review of 135 lesions in 12 patients by Choi et al 59 assessed the predictive value of FDG-PET/CT parameters in predicting response to radiotherapy. They found that treatment failed more often when biologically effective dose was low and when SUVmax increased after intervention.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Interestingly, the observed posttreatment decreases in SUVmax did not seem to be related to radiation site, irradiated volume, or dose. 59 Despite the apparent efficacy and advantages of FDG-PET/CT imaging in detecting MS, it is still recommended to order CT and MRI imaging when extramedullary disease is suspected. 37…”
Section: Radiation Therapymentioning
confidence: 99%